Knowledge networks in innovation among small KIBS firms. Issue 5 (1st September 2011) - Siikonen, Jukka; Pellikka, Jarkko; Littunen, Hannu
Supporting the commercialisation processes in small knowledge-intensive firms has been a primary objective of both national and regional innovation policies. This study provides empirical evidence of the external collaboration during commercialisation processes based on a survey of 213 small knowledge-intensive business services (KIBS) firms. The findings show that these firms have used two types of network relationships for their innovation creation and commercialisation: Based on these classifications, policy implications and recommendations for both policy-makers and small KIBS managers are provided.